Students Virtuality Perception in Pandemic; towards the new-U - Pineda Torres, Franklin
In order to continue the academic processes in the pandemic time, face-to-face universities had to resort very quickly to the virtual format and remote class. It is observed that the virtual coupling from the communicative, pedagogical and technological dimensions has been a challenge for the actors within the university, among them, the students who see virtuality as a valuable tool; virtuality is necessary but not sufficient, it is a educational partial substitute that requires improvements for the university new reality, such as: interaction in class, motivation, university well-being, laboratories, time management and academic activities among the most important.